Pemahaman Akutansi, Sistem Pengendalian Internal Dan Teknologi Informasi Yang Mempengaruhi Kualitas Laporan Keuangan Pada Era Pandemi Covid-19 (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The purpose of this study was to determine the effect of understanding accounting, internal control systems and information technology on the quality of CV's financial reports. Woodpoindo Semarang in the Era of the Covid-19 Pandemic. The population in this study are managers and their staff and the financial management section, while the sample is 45 employees. The research data were tested for normality with classical assumptions and processed with the SPSS Version 23.0 program, then analyzed using multiple linear regression. The results of the study are as follows: 1.) Understanding of accounting has no effect on the quality of financial reports as evidenced by the t-value of 0.468 which is less than the t-table value of 1.682 and the significance number of 0.642 is greater than the α value of 0.05. Thus H1 is rejected. 2.) The internal control system has a positive effect on the quality of financial reports as evidenced by the t-count value of 19.785 greater than the t-table value of 1.682 and a significance number of 0.000 which is less than the α value of 0.05. Thus, H2 is accepted. 3.) Information technology has an effect on the quality of financial reports as evidenced by the t-count value of 3.576 greater than the t-table value of 1.682 and a significance number of 0.001 which is less than the α value of 0.05. Thus, H3 is accepted.